A Comparison of Modern Wage Decomposition Approaches - Behr, Andreas (Journal of Income Distribution®, 2015)
During the last three decades the decomposition method originally suggested to explain differences in mean wages has been considerably extended. In more recent approaches the focus has turned towards analyzing complete income distributions and differences between groups' incomes at all percentiles. We discuss in detail and apply four approaches: firstly, the approach of Juhn, Murphy and Pierce (1991, 1993), the approach suggested by Machado and Mata (2001, 2005), the approach suggested by Donald, Green and Paarsch (2000) and finally, the approach suggested by DiNardo et al. (1996) and Fortin and Lemieux (1998). In this paper, we compare these approaches and decompose differences in men's wage distributions between the USA and Germany in 2007.